CENTROID-MOMENT TENSOR SOLUTIONS FOR OCTOBER DECEMBER 1990 - Dziewonski, A; Ekstrom, G; Woodhouse, J; Zwart, G (1991)
Centroid-moment tensor solutions are presented for 199 earthquakes that occurred during the fourth quarter of 1990. The solutions are obtained using corrections for aspherical Earth structure. © 1991.